2018
DOI: 10.1590/s0102-053620180205
|View full text |Cite
|
Sign up to set email alerts
|

Increase in pea productivity associated with irrigation management

Abstract: Proper irrigation management is crucial to obtain high yields of pea, since its cultivation is recommended in cold and dry seasons. Taking into account the great genetic diversity, we considered necessary to evaluate cultivars which best adapt to the intrinsic conditions of Cerrado Region, as it presents low fertility soil, long dry period in the winter, drought periods (veranicos) in rainy season, mainly in January and February (summer). Thus, the aim of this study was to evaluate adaptability of green-pea cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…For the variables number of pods per plant and mass of pods per plant, no data were found in the literature on the estimation of plot size to evaluate these variables, leading to a wide variation in plot sizes used in the work with the crop. The plot sizes used by Cardoso et al (2012); Santos, Cunha, Taira, Souza, and Leal (2018); Singh et al (2019);and Zhang et al (2016) ranged from 10 to 420 plants per plot, which were higher than those obtained in the present study, thus indicating greater reliability in the published information. However, Carvalho, Rezende, Aquino, Freitas, and Oliveira (2012); Garcia, Ferreira, Figueiredo, and Santos (2010); Mahieu et al (2009); and Oliveira, Carvalho, Rezende, and Freitas (2011) used a plot size ranging from one to six plants; these values are below what was estimated in the present study and may have led to less experimental precision in these works.…”
Section: Plot Sizecontrasting
confidence: 64%
See 1 more Smart Citation
“…For the variables number of pods per plant and mass of pods per plant, no data were found in the literature on the estimation of plot size to evaluate these variables, leading to a wide variation in plot sizes used in the work with the crop. The plot sizes used by Cardoso et al (2012); Santos, Cunha, Taira, Souza, and Leal (2018); Singh et al (2019);and Zhang et al (2016) ranged from 10 to 420 plants per plot, which were higher than those obtained in the present study, thus indicating greater reliability in the published information. However, Carvalho, Rezende, Aquino, Freitas, and Oliveira (2012); Garcia, Ferreira, Figueiredo, and Santos (2010); Mahieu et al (2009); and Oliveira, Carvalho, Rezende, and Freitas (2011) used a plot size ranging from one to six plants; these values are below what was estimated in the present study and may have led to less experimental precision in these works.…”
Section: Plot Sizecontrasting
confidence: 64%
“…The plot sizes used by Cardoso et al. (2012); Santos, Cunha, Taira, Souza, and Leal (2018); Singh et al. (2019); and Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Corn ET was estimated using the modified FAO method (MFAO) (Bernardo et al, 2019;Mantovani et al, 2006). The MFAO method has been widely used in scientific studies in Brazil (Santos et al, 2018;Silva et al, 2018c;Venancio et al, 2019;Vicente et al, 2017). In addition, it has been widely applied in several Brazilians farms and in other countries by the company IRRIGER (http://www.irriger.com.br/ en-US/) (IRRIGER, 2019).…”
Section: Modified Fao Methodsmentioning
confidence: 99%
“…Improper irrigation scheduling with deficit quantity of water has led to water stress in pea production, causing a decrease in the evapotranspiration, growth parameters and pea yield [1]. Harmful effects of improper water management, such asover application of water, deficit application of water, effect of water on soil salinity, water stress, and lack of research to determine the optimum quantity of water in pea production, have been reported by many researchers [1][2][3]. An irrigation moisture regimen for green pea crop is crucial to optimize yield and avoid over-watering.…”
Section: Introductionmentioning
confidence: 99%
“…Different varieties of green pea with varying irrigation levels, viz., 50%, 75%, 100%, and 125% ETc were tested under the drip irrigation and found a decrease in the productivity of pea at an excess and deficit irrigation treatments [3]. Green pod yield decreased with an increase in drought conditions, occurringat the vegetative and flowering stages [6].…”
Section: Introductionmentioning
confidence: 99%